Silicon‐Microtube Scaffold Decorated with Anatase TiO2 as a Negative Electrode for a 3D Litium‐Ion Microbattery. Issue 8 (27th January 2014) - Eustache, Etienne; Tilmant, Pascal; Morgenroth, Laurence; Roussel, Pascal; Patriarche, Gilles; Troadec, David; Rolland, Nathalie; Brousse, Thierry; Lethien, Christophe
<x xml:space="preserve">Abstract</x> An optimized scaffold based on silicon microtubes is designed to increase the surface capacity of 3D lithium‐ion microbatteries. High‐depth, mechanically robust microstructures are fabricated using microelectronic facilities. Conformal deposition of anatase TiO2 is achieved using atomic layer deposition, realizing the targeted improvement for microbatteries; a surface capacity of 0.2 mA h cm–2 at a charge rate of C/10 is obtained in standard liquid electrolyte. This work paves the way for the fabrication of solid‐state 3D Li‐ion microbatteries with an efficient 3D scaffold.